Proximate mechanisms determining size variability in natterjack toads - Sinsch, U. (2010)
In the toad Bufo calamita, among-population variation of size follows roughly a converse Bergmann cline, but populations exist that do not fit this pattern. We propose that latitudinal body size variation is a byproduct of adaptive covariation among the life-history traits juvenile growth rate, longevity and lifetime fecundity. We choose five populations (two in Andalusia, two in Catalonia and one in Rhineland-Palatinate) representing a variation of adult size from 39 mm to 95 mm snout-vent length, a latitudinal gradient from 37 to 50° and an altitudinal gradient from sea level to 420 m. Skeletochronology was used to estimate the age-related life-history traits of 313 toads and their lifetime pattern of growth. At southern latitudes, toads matured and reproduced earlier than those at northern latitudes, but had a reduced potential reproductive lifespan due to lower longevity. Age-adjusted adult size depended mainly on the size achieved between metamorphosis and first hibernation or aestivation, which in turn was influenced by local factors. We propose that first-year size corresponds to the duration of the aboveground activity period, temperature during the activity period and the type of shelter sites and hibernacula available in the habitat. After attaining sexual maturity, the growth rates did not differ among populations. Interactions of multiple environmental factors during the first year of life determine age at maturity, adult size and size variation among populations. Local body size and potential reproductive lifespan covary to optimize lifetime fecundity throughout the geographical range. The presence of a small-sized population in southern Spain does not fit the pattern predicted by a converse Bergmann cline, but is compatible with the hypothesis that body size variation among B. calamita populations may be the evolutionary byproduct of optimized lifetime fecundity.